19.2k views
23 votes
Solving quadratic inequalities

Solving quadratic inequalities-example-1
User Cantsay
by
5.7k points

1 Answer

4 votes

Answer:


\boxed{\sf x < -3\quad \mathrm{or}\quad \:x > -1}

Explanation:


\sf x^2+4x+3 > \:0

In order to solve inequality, we need to factor the left hand side. we can use the transformation
ax^2+bx+c=a(x-x_1)(x-x_2) to factor quadratic polynomials. where x(1) & x(2) are the solutions of the quadratic equation ax²+bx+c=0 .


\sf x^2+4x+3=0

Quadratic formula:-


\boxed{\sf x_(1,\:2)=(-b\pm √(b^2-4ac))/(2a)}


\sf a=1\\b=4\\c=3


\sf \cfrac{-4\pm √(4^2-4* \:1* \:3)}{2* \:1} ← Calculate


\sf √(4^2-4* \:1* \:3)=\boxed{2}


\sf \cfrac{-4\pm \:2}{2* \:1}

Now, let's Separate the solutions,


\sf x_1=\cfrac{-4+2}{2* \:1},\:x_2=\cfrac{-4-2}{2* \:1}

Do the calculations,


\sf x_1=\cfrac{-4+2}{2* \:1}=\boxed{-1}


\sf x_2=\cfrac{-4-2}{2* \:1}=\boxed{-3}


\boxed{\sf x < -1\quad \mathrm{or}\quad \:x > -3}

User Fred Zimmerman
by
4.4k points